2017
DOI: 10.1111/jasp.12451
|View full text |Cite
|
Sign up to set email alerts
|

Need for closure and reactions to innovation

Abstract: Although prior research on need for closure (NFC) has shown that it can lead individuals to dislike change, the mechanisms underlying that dislike were unclear. The current studies extend previous findings by investigating a mediating mechanism that may explain high NFC individuals’ dislike of change. In two studies using Italian (N = 852) and American (N = 94) samples, we hypothesized that high NFC individuals would have lower intentions to use new technological developments, and that this relationship would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
1
5
0
3
Order By: Relevance
“…This is also linked to resistance to new ideas and experiences, and thus to resistance to change [51]. Chernikova et al [52] showed that a higher level of Closed-mindedness was associated with stronger anxiety towards new technologies and lower willingness to use them. Thus, persons with this type of epistemic motivation avoid contact with new technologies, and for this reason may exhibit lower levels of dysfunctional behavior connected with such technologies.…”
Section: Discussionmentioning
confidence: 99%
“…This is also linked to resistance to new ideas and experiences, and thus to resistance to change [51]. Chernikova et al [52] showed that a higher level of Closed-mindedness was associated with stronger anxiety towards new technologies and lower willingness to use them. Thus, persons with this type of epistemic motivation avoid contact with new technologies, and for this reason may exhibit lower levels of dysfunctional behavior connected with such technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Этому явлению можно противопоставить стремление к когнитивной открытости, предполагающей способность воспринимать разнообразные сведения, выдерживать противоречия, интегрировать конфликтующие концепты или находить компромиссы [5]. В концепции эпистемической мотивации А. Круглянски, стремление к закрытию имеет целью снизить тревожность от неопределенности [37].…”
Section: когнитивное обеспечение процессов интеграцииunclassified
“…For instance, NFCC can be manipulated through time pressure, noise, fear of invalidity, or task attractiveness (Heaton & Kruglanski, 1991;Kruglanski & Freund, 1983;Roets at el., 2008;Webster, 1993). Importantly, NFCC has been shown of great relevance for various organizationally relevant outcomes, such as creativity or resistance to innovation (e.g., Chernikova, Kruglanski, Giovannini, Vezzali, & Su, 2017;Chirumbolo, Livi, Mannetti, Pierro, & Kruglanksi, 2004;Pierro, Kruglanski, & Raven, 2012).…”
Section: Cognitive Factors In Diversity Effectsmentioning
confidence: 99%